Recent advances in porous MOFs and their hybrids for photothermal cancer therapy - Su, Jia; Jing, Peng; Jiang, Ke; Du, Jingjing (Dalton transactions : an international journal of inorganic chemistry, 2022)
Cancer is still one of the most life-threatening diseases in the world. Among the various cancer therapeutic strategies, photothermal therapy (PTT) has attracted considerable attention due to its high treatment efficacy, low invasive burden, and minor side effects. Microporous metal-organic frameworks (MOFs) are potential materials for photothermal tumor treatment thanks to their high surface areas, suitable pore geometry, and easy functionalization. Through designating organic linkers, encapsulating PTT agents and fabricating MOF hybrids, MOF-based treatment platforms have great potential in PTT. In this review, we mainly summarize the recent advances of MOFs in photothermal combined cancer therapy. The present challenges and possible future prospects in this field are also explored. We mainly summarize the recent advances of MOFs in photothermal combined cancer therapy and hope that this review will stimulate more interesting explorations in MOFs for photothermal therapy.